2006
DOI: 10.5551/jat.13.247
|View full text |Cite
|
Sign up to set email alerts
|

Decreases in Serum Triacylglycerol and Visceral Fat Mediated by Dietary Soybean .BETA.-conglycinin

Abstract: Soy protein isolate (SPI) is known to reduce the risk of heart disease by lowering serum cholesterol and triacylglycerol (TG) levels. Soybean -conglycinin, which is a component of SPI, might be the active ingredient that prevents and/or ameliorates lifestyle-related diseases, such as hyperlipidemia and obesity. This study aimed to determine the efficacy of soybean -conglycinin for lowering the human serum TG level and visceral fat. Randomized double-blind placebo-controlled designs were used to test the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 16 publications
5
112
2
Order By: Relevance
“…20 Some studies in animals and human subjects have shown a significant HC effect of dietary soybean protein. 1,11,12 In this study, we examined the effects of different doses of bconglycinin in rats that had received HC diet. At the end of the 28-day treatment there were no differences in the animals' growth among groups during the experimental period.…”
Section: Resultsmentioning
confidence: 99%
“…20 Some studies in animals and human subjects have shown a significant HC effect of dietary soybean protein. 1,11,12 In this study, we examined the effects of different doses of bconglycinin in rats that had received HC diet. At the end of the 28-day treatment there were no differences in the animals' growth among groups during the experimental period.…”
Section: Resultsmentioning
confidence: 99%
“…12 The soybased formula food in the present trial consisted of 12 g of SP, which contains 1.5-2.0 g of β-conglycinin. The difference in the amounts of β-conglycinin may lead to different results.…”
Section: Formula Food With Soy Protein Vs Milk Proteinmentioning
confidence: 99%
“…8,26) Recently, it was reported that -conglycinin contributes at least in part to the TG-lowering effects of SPI. 27) Thus it is thought that SPI has physiological functions that improve both cholesterol and TG levels.…”
Section: Discussionmentioning
confidence: 99%